Performance of intacta soybean cultivars in Marechal Cândido Rondon, Western Paraná State - Tessele, Augusto; Kreinchinski, Fabio Henrique; Albrecht, Leandro Paiola; Albrecht, Alfredo Junior Paiola; Lorenzetti, Juliano Borotoluzzi (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The soybean, one of the most important crops in Brazilian agriculture, is a profitable crop due the use of new technologies in the development of new cultivars, which contain more biotechnologies that turn its management easier. Among these technologies, there is the INTACTA RR2 PRO®, which was recently released. However, there are few studies to show the most yielding cultivars indicated to Marechal Cândido Rondonm,Paraná State, Brazil. Therefore, the aim of this study was to evaluate the performance of some IPRO soybean cultivars recommended or cultivated in Western Paraná and identify the most yielding ones. A couple of agronomic characteristics were evaluated, focusing in the yield and cycle. The randomized block design was used, with four replications. The data was submitted to variance analysis and the averages were compared following the Tukey Test (p ≤ 0.05). The results indicate that the cultivars with the shortest cycles are more adapted and provided the highest yields in the region.